Combined modality neoadjuvant treatment for stage III/IV melanoma with PD-1 blockade plus radiation: A case series. (2017) - Alevizakos, Michail; Ollila, David W.; Chera, Bhishamjit S.; Dodd, Leslie G.; Kish, Joshua B.; Moschos, Stergios J.
Abstract: Purpose: Over the last 6 years, 8 treatments were FDA-approved for patients with distant metastatic cutaneous melanoma on the basis of prolonged overall survival. Several of these treatments are either FDA-approved or in advanced stages of clinical development in the adjuvant setting for patients with high risk for relapse melanoma. The neoadjuvant setting provides even greater opportunities to incorporate these treatments into a more effective multimodality management. While most neoadjuvant strategies involve single modality approach to date, the ability of radiation therapy to synergize with immunotherapies in distant metastatic melanoma should also be considered in the neoadjuvant setting. Methods and results: 4 patients with unresectable stage III melanoma were treated with PD-1 inhibitors and concurrently received hypofractionated radiation therapy. This regimen not only rendered their surgery feasible, but also resulted in complete pathologic response in two of these patients without inducing any serious adverse events or surgical complications. Furthermore, we present clinicopathologic and molecular data that may in part explain differences in complete pathologic response among these four subjects. Conclusions: In this limited case series, our neoadjuvant combined modality regimen was effective and well tolerated. Concurrent PD-1 blockade with radiation therapy that could readily be applied into daily oncology practice is not limited in particular patient subgroups (e.g. BRAFV600-mutant) and may have a better toxicity profile than concurrent immune checkpoint blockade.